Methods of Jet Control in Ventilation - Mileikovskyi, V. (КНУБА, 2017)
Inlet jet parameters are one of the influencing factors on microclimate parameters in rooms. There are many solutions of air distributing technique. Some of them are widespread; others are special purposes solutions and applied on sporadic objects. Nevertheless, there is not enough detailed classification of jet control methods, used in the air distributing solutions. In this work, such classification is proposed, based on thousands of inventors certificates and patents. For easier classification, the methods are systematized by four main groups: with flow turbulization, without significant turbulization, with flow stabilization and combined. Possibilities of jet range change is also shown. This classification is upgradable during the development of air distribution technique.
Способи керування струминами у вентиляції
Способы управления струями в вентиляции
Keywords: air distribution; jet; ventilation; air exchange; 697.92